Anarchism, postmodernism and realism under confirmatory bias - Juan Urrutia Elejalde (SERIEs - Journal of the Spanish Economic Association, 2012)
In order to revamp Rhetoric as a methodological approach in Economics, this paper combines natural selection in evolution and the psychology of confirmatory bias. This latter can be thought of as a second best adaptation to the forces of natural selection and can also be an evolutionary stable strategy so that it is here to stay as seems to be supported by several psychological experiments. But once confirmatory bias is at work it is quite clear that economic agents in general or scientists in particular do not act as perfectly rational in the sense that they do no mimic the behavior of a Bayesian statistician. This combination has yielded three main results. First honest and open, power-free, conversations may not preclude systematic error in appreciation of theories. Therefore the moral constraint supposedly operating on the opinions of scientists might not be binding in the sense that their opinions might look completely anarchistic. Second the social constraint might also be not binding because each scientist opinion carries the same weight regardless of fame or honor, a very postmodern situation. Third, one can be a supporter of the correspondence theory of truth, one can have no doubts about the existence of an independent underlying real world and yet one might be obliged to accept that an honest and informed conversation may lead to the acceptance of false theories.
Keywords: B41; 330; rhetoric of economics; natural selection; confirmatory bias; Evolutionsökonomik; Wirtschaftspsychologie; Dogmengeschichte